Individual factors related to acceptance of mentally retarded adolescent by their family - Taghavi Larijani T; Monjamed Z; Mehran A; Gharahi Ghehi F (Tehran University of Medical Sciences, 2006)
Background & Aim: Disorders of intelligence is associate with lack of growth in physical, social and educational dimensions. Also it can cause many problems for patient and their family in context of care and maintenance of patient. Psychiatric nurse recognize this problems and helping to resolve them. They can play the effective role to acceptance of mentally retarded adolescent by their family. Methods & Materials: This research is a descriptive analytical cross-sectional study. Out of research population 406 subject were selected among sponsors of mentally retarded adolescent through convenient sampling (199 subjects had accepted their young adults in their families "daily class" and 207 subjects who had repelled their mentally retarded children "nightly class") Data were collected through interview and filling questionnaire. And then were analyzed through SPSS software by using descriptive statistics and statistical tests like χ2 and t-test (in depended group). Results: Findings of this research showed that among demographic characteristics of clients like age, level of education, causes and extent of mental-retardedness of Adolescents and acceptance by the family there is a significant correlation (p<0.05). There are also meaningful relation among individual factor such as ability to wear clothes, ability to feed, observing individual hygiene, precedence of lack of control on urine and stool, precedence of sleep disorder in form of insomnia, record of sensitivity and quick resentment, affliction to psychological disease, the problem of setting up communication with others, profile of hurting oneself and others, making noise and disturbance for others and background of escaping from home, and acceptance of mentally retarded young adult by family (df=1 p<0.001).